ENHANCING VEHICLE SPEED MEASUREMENT WITH WEB-BASED CAMERA INTEGRATION - Wibowo, Helmi; Sugiyarto, Sugiyarto; Febriansyah, Nuril Akbar (Teknik Elektro Universitas Siliwangi, 2024)
Currently there is a development of speed measuring devices, but the testing process is still lacking ergonomics and safety factors. There are still many Speedometers with no storage of results or less informative printed evidence such as passing information and lack of monitoring aids such as cameras. This research is a development research using the Research and Development (RD) level 3 method, namely conducting research on existing products and testing the effectiveness of these products. The design of this tool consists of inputs, namely laser sensors, push buttons, batteries, and power supplies. Then the control uses arduino nano and ESP32 with the output of a thermal printer, website, and 20×4 LCD. The performance of the tool is good, works according to the design, and reads well and clearly. The website is valid, works well, and as expected. Camera performance is good enough when connected to a laptop through the DroidCam application. Based on the results of testing the tool using 50 vehicle samples with the results of an average error value of 2.23% or equal to 0.89 km / hour. While the average accuracy or success rate of the measurement results is 97.77%. There are 5 error measurements from 50 vehicle samples or there is 1 error vehicle every 10 measurements.